DESEMPENHO ZOOTÉCNICO E HEMATOLOGIA DE TRAÍRA HOPLIAS MALABARICUS - OLIVEIRA, Beatriz Pacheco Nogueira; OLIVEIRA, Fúlvia Cristina; SANTO, Fayane Espírito; CALVES, Gleice de Souza; SILVA, Leonardo Augusto; CAMPOS, Cristiane Meldau (ANAIS DO ENIC, 2018)
-